Geographical distribution of ALDH2 rs671 polymorphism in Chinese angina pectoris patients - Dong, Wenjia; Yu, Junjie; Xu, Siqi; Li, Hongsheng (Frontiers in Genetics, 2025)
BackgroundMitochondrial acetaldehyde dehydrogenase 2 (ALDH2) plays a critical role in the metabolism of ethanol and nitroglycerin. Mutations in ALDH2 reduce enzymatic activity, impairing nitroglycerin metabolism. ALDH2 genetic polymorphisms exhibit significant regional variations across China. This study investigates the distribution of ALDH2 allelic and genotypic frequencies in patients with angina pectoris across northern (Luoyang, Henan), eastern (Jiaxing, Zhejiang), and southern (Guilin, Guangxi) China, and explores the relationship between ALDH2 genotypes and selected clinical characteristics.Materials and MethodsA total of 1,084 angina pectoris patients were recruited from the three aforementioned regions. ALDH2 genotyping was performed using fluorescence quantitative PCR, and associations between genotypes and clinical characteristics, such as smoking and alcohol consumption histories, were analyzed.ResultsThe geographical distribution of the ALDH2 rs671 G→A mutation showed a significant increase in mutation frequency from northern to southern China. Genotypic distributions differed significantly across regions, with GG being predominant in northern China and higher frequencies of GA and AA observed in southern regions. Additionally, lifestyle factors such as smoking and alcohol consumption were significantly associated with the presence of the A allele, reflecting the interplay between genetics and environmental influences.ConclusionThis study reveals significant regional differences in ALDH2 rs671 polymorphism and its association with lifestyle factors in angina pectoris patients across China. Since the ALDH2*2 variant markedly reduces the metabolic activation of nitroglycerin, these findings have important clinical implications: in regions with a higher prevalence of the A allele, patients may exhibit reduced therapeutic response to nitroglycerin. This highlights the need for region-specific and genotype-informed strategies in the management of angina pectoris.